2011
DOI: 10.3844/ajavsp.2011.73.76
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nifedipine on Dichlorvos-Induced Seizure in Mice

Abstract: Problem statement: Dichlorvos a synthetic organophosphate poisons is the property of insecticide. These toxins as insecticides in agriculture and medicine for animals and the destruction of ectoparasites can be used. Studies have shown that Dichlorvos creation seizure effects in different animals. Nifedipine, dihydropyridine calcium channel blockers, widely used for treatment of cardiovascular diseases. Studies have shown that the calcium channel blockers are anticonvulsant effects in different animal models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…So, aminophylline induced clonic/tonic-clonic seizures in a dose-dependent manner and this is in agreement with earlier reports in this regard. 5,10,19 Though aminophylline has got antioxidant property the present study it was also found that it generate sufficient amount of free radicals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…So, aminophylline induced clonic/tonic-clonic seizures in a dose-dependent manner and this is in agreement with earlier reports in this regard. 5,10,19 Though aminophylline has got antioxidant property the present study it was also found that it generate sufficient amount of free radicals.…”
Section: Discussionmentioning
confidence: 96%
“…3 These repetitive, generalized seizures are commonly fatal and no specific, pharmacologically antagonistic drug is known. 4 In an attempt to evaluate the mechanisms involved in this phenomenon, several studies have been implicated for one or the other mode of action, 5,6 but no clear-cut consensus regarding the toxicodynamics of theophylline-induced seizures has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Exposures to OPs are source of significant quantity of poisonings that affect various organs such as skeletal muscles, GI tract, bladder, secretory glands, CNS, and respiratory systems and create many signs and symptoms such as weakness, glandular secretion, fasciculation, acute pancreatitis, convulsion, respiratory depression, and finally death [ 10 , 11 ]. Centrally mediated seizures and convulsions are one of the toxic signs that happen following poisoning with organophosphorus (OP) anticholinesterase such as Dichlorvos [ 12 , 13 ]. Since treatment of this life-threatening effect of OP compounds is very importants so the aim of this study was to determine the effect of diazoxide (potassium channel opener) on Dichlorvos-induced seizures in mice.…”
Section: Introductionmentioning
confidence: 99%
“…An innate immune response is mediated by microglia that contributes to the progression of the diseases. Activated microglia produce several proinflammatory and neurotoxic mediators including complement, cytokines, chemokines, acid arashidonic and its metabolites and reactive oxygen and nitrogen species, several of which contribute directly to neuronal injury (Perrone et al, 2010;Mirhadi, 2011). Alterations in the microenvironment such as microglial inflammation and the release of proinflammatory cytokines may affect normal cell proliferation and differentiation, which could cause ectopic neurogenesis, astrogliosis and ectopic synaptic reorganization (Haiju et al, 2009).…”
Section: Introductionmentioning
confidence: 99%